Biochemical profiling of metabolomics in heavy metal-intoxicated impaired metabolism and its amelioration using plant-based bioactive compound - Yaqoob, Azka; Rehman, Kanwal; Akash, Muhammad Sajid Hamid; Alvi, Maria; Shoaib, Syed Muhammad (Frontiers in Molecular Biosciences, 2022)
Exposure to Pb is widely spreading and has far-reaching negative effects on living systems. This study aimed to investigate the toxic effects of Pb, through biochemical profiling and ameliorative effects of quercetin against Pb-toxicity. 25 male Wister albino mice were divided into following 5 groups. CON-group received normal saline; Pb-group received PbAc; Pb+Q-CRN group received lead acetate followed by quercetin; Q-CRN group received quercetin; CRN group received corn oil. After 4 weeks, the mice were sacrificed. It was speculated that Pb significantly increased the level of serine, threonine, and asparagine and decreased the levels of valine, lysine, and glutamic acid in the plasma of Pb-group thus impairing amino acid metabolism. But in Pb+Q-CRN group, the level of these 6 amino acids was restored significantly due to the ameliorative effect of quercetin. The presence of lipid metabolites (L-carnitine, sphinganine, phytosphingosine, and lysophosphatidylcholine) in mice serum was confirmed by ESI/MS. The GPx, SOD, GSH, and CAT levels were significantly decreased and the MDA level was significantly increased thus confirming the oxidative stress and lipid peroxidation in Pb group. Antioxidant effect of quercetin was elucidated in Pb+Q-CRN group. Expression of CPT-I, CPT-II, LCAT, CROT, CACT, and MTR genes was significantly upregulated in liver of Pb goup mice. Hence the findings of this study proved that Pb exposure induced oxidative stress, upregulated the gene expression, and impaired the lipid and amino acid metabolism in mice.